Wheat Improvement, Management and Utilization - Wanyera, Ruth; Owuoche, James (IntechOpen, 2017)
The Wheat Improvement, Management, and Utilization book covers some of the most recent research areas that touch on enhancement of wheat productivity. It is obvious that wheat is one of the major staple crops grown globally. This crop has widely been researched on considering that, for instance, it is afflicted by various abiotic and biotic stresses that limit its growth and productivity. Today?s goal of wheat improvement consistently is to develop varieties that are high yielding with good processing and technological qualities, well adapted and tolerant to prevailing biotic and abiotic stresses. Therefore, this is a valuable reference book on wheat improvement, agronomy, and end-use qualities, particularly for those who work in research organizations and higher academic institutions. Moreover, it provides an invaluable resource for readers interested in a quick review of trending topics in wheat.